High‐Z Nanostructured Ceramics in Radiotherapy: First Evidence of Ta2O5‐Induced Dose Enhancement on Radioresistant Cancer Cells in an MV Photon Field. (16th October 2013) - Brown, Ryan; Tehei, Moeava; Oktaria, Sianne; Briggs, Adam; Stewart, Callum; Konstantinov, Konstantin; Rosenfeld, Anatoly; Corde, Stephanie; Lerch, Michael
<x xml:space="preserve">Abstract</x> This article pioneers a study into the use of the tantalum pentoxide nanoceramics as novel candidates for dose enhancement radiotherapy. It is revealed that a significant induced dose enhancement on radioresistant cancer cells expose to tantalum pentoxide nanoparticles and irradiated with 10 MV. In this study, in vitro experiments are performed. The radiobiological endpoint is clonogenic survival. We exposed 9L gliosarcoma cells to the nanoparticles at 50–500 μg mL−1 range and observed concentration‐dependent toxicity. Irradiation of the exposed and unexposed cells with 10 MV X‐ray photons reveals a sensitization enhancement ratio of 1.33. The associated cell survival curves demonstrate a significant change in shape, indicative of increased lethality of the local radiation environment. We postulate that this enhancement is primarily due to secondary electrons produced from photoelectric interaction and pair production, with backscattering on nanoparticle aggregates leading to increased radiobiological effectiveness.